Determinants of Rural-Women Farmers Decisions on Artisanal Refinery Activities and Agricultural Productivity in Emohua Local Government Area, Rivers State, Nigeria - Unaeze, Henry Chiaka; Godstime, Emenike, Chimdioso (An Overview on Business, Management and Economics Research Vol. 3, 2023)
This study hinged on determinants of Rural-Women-farmers decisions on artisanal refineries activities and Agricultural Productivity in Emohua Local Government Area of Rivers State, Nigeria. A total of eighty respondents were selected from four communities in the study area using a purposive sampling technique. Data were collected using a well-structured questionnaire. Descriptive statistics and bivariate probit regression model were used in the assessment. The results revealed that majority (100%) of the respondents were female while their mean age was 36years. Majorities (45.0%) of the respondents are widows and their average income was (#421,250.00k). The demand-pull diversification option was sales of petroleum products (27.1%) which were the major findings of this study. This diversification option resulted to negligence of farming activities by the rural women in the study area. It was only (25.4%) who attested that sensitization program to curb artisanal refinery activities was the major intervention program carried out by the state government, while only (33.0%) accentuated that accidental and sudden death was their major constraint. The result from the bivariate probit regression model showed that age (0.027209), farming experience (0.043173) and household size (0.044784) were statistically significant and positive to influence their decisions while income (2.24E-07), schooling (-0.022025) and number of farmlands destroyed by oil spills (-0.113430) were negative. Therefore, government should encourage the establishment of modular refineries to save the environment of continuous pollution and curb rurallivlihood drift.